Methyl-CpG binding protein 2 expression is associated with symptom severity in patients with PTSD in a sex-dependent manner - Cosentino, Livia; Witt, Stephanie; Dukal, Helene; Zidda, Francesca; Siehl, Sebastian; Flor, Herta; De Filippis, Bianca (Translational Psychiatry, 2023)
Traumatic events may lead to post-traumatic stress disorder (PTSD), with higher prevalence in women. Adverse childhood experiences (ACE) increase PTSD risk in adulthood. Epigenetic mechanisms play important roles in PTSD pathogenesis and a mutation in the methyl-CpG binding protein 2 (MECP2) in mice provide susceptibility to PTSD-like alterations, with sex-dependent biological signatures. The present study examined whether the increased risk of PTSD associated with ACE exposure is accompanied by reduced MECP2 blood levels in humans, with an influence of sex. MECP2 mRNA levels were analyzed in the blood of 132 subjects (58 women). Participants were interviewed to assess PTSD symptomatology, and asked to retrospectively report ACE. Among trauma-exposed women, MECP2 downregulation was associated with the intensification of PTSD symptoms linked to ACE exposure. MECP2 expression emerges as a potential contributor to post-trauma pathophysiology fostering novel studies on the molecular mechanisms underlying its potential sex-dependent role in PTSD onset and progression.